Assessing The Implications Of CBDR-RC Principle Implementation In Indonesia’s NDC: A Review Of Climate Change Mitigation - Septika Nanda Arifia; Sri Wartini (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Climate change has emerged as a serious threat to both humanity and the global ecosystem, necessitating a coordinated global response. The Paris Agreement embodies these efforts by emphasizing the principle of Common but Differentiated Responsibilities and Respective Capabilities (CBDR-RC), which underscores the awareness of shared responsibility with varying capacities among nations. This principle is reflected in the Nationally Determined Contributions (NDCs), serving as tangible manifestations of each country's commitment. This research addresses two main issues: Firstly, why is the CBDR-RC principle the foundation for implementing NDCs in Indonesia? Secondly, to what extent does the implementation of NDCs in Indonesia align with the CBDR-RC principle and Indonesia's commitments in the Paris Agreement to achieve sustainable development and address climate change? This study the study utilizes legislative, comparative, conceptual, and historical methodologies. Findings reveal that the CBDR-RC principle forms the basis of NDC implementation in Indonesia, grounded in Indonesia's membership status in the Paris Agreement. However, practical execution falls short, revealing a disparity between idealism and reality in realizing commitments and ambitions to address climate change.